Segmental neurofibromatosis. - Pisani, V. (European Journal of Pediatric Dermatology, 2014)
Peripheral neurofibromatosis (NF1) is present in 1 : 3000 newborns, while segmental NF1 in 1 : 40,000 (1, 2). In NF1 café-au-lait spots represent the earliest sign, while classic neurofibromas appear towards the end of the second decade of life. This symptom dualism is even more evident in segmental NF1. In infantile forms there are never classic neurofibromas but only plexiform neurofibromas, whereas in the adult forms are often present only neurofibromas while café-au-lait spots lack. It is possible that this difference depends on the fact that café-au-lait spots are related to a mutation present in the fibroblasts, whereas a mutation in the Schwann cells is responsible for neurofibromas (2). It is likely that the mental retardation in our patient is not due to the mutation responsible for segmental NF1, but to hypoxic-ischemic encephalopathy.